Towards a cold atom gravimeter - Chew, Andrew (2013)
This thesis describes the construction of a portable cold atom gravimeter with the aim to be employed in remote locations. Two species of alkali atoms would be eventually used, namely Rubidium-87 and Cesium-133. The advantage of such a system is shorter duty cycle, and shorter dead time. In this thesis we focus on the experimental realization of a Rubidium-87 gravimeter, using the Ramsey-Bord´e interferometry method first described by C. Bord´e, and employed by Kasevich et. al. Approximately 10^8 atoms are laser cooled and trapped to a MOT and further cooled by a optical molasses to a temperature of 12μK. Two counterpropagating Raman beams separated by a frequency matching the ground state hyperfine splitting will be used to excite stimulated Raman transitions to place the atoms into a superposition of the two ground metastable states. This thesis describes in detail the vacuum system and the laser systems built to cool and trap the atoms and to produce the Raman beams to perform the Ramsey sequence. The thesis covers also the relevant theory related to our experiment.